Foraging ecology of urban-breeding merlins (Falco columbarius) - Sodhi, Navjot Singh (1991)
I studied the foraging ecology of breeding Merlins (Falco columbarius) in Saskatoon (Canada) from May to July,1987-90. I identified 1332 prey items belonging to 36 vertebrate species from prey remains collected near 65 Merlin nests. The principal prey of breeding Merlins was the House Sparrow (Passer domesticus), which along with the Horned Lark (Eremophila alpestris) were usually taken more frequently than expected from their relative abundance in the environment. other potential prey species were usually taken in proportion to, or less than expected. The proportion of adult House Sparrows in the diet decreased while that of juveniles increased significantly as the Merlin breeding season progressed. During the incubation and nestling periods, the relative abundance of male and female House Sparrows did not differ significantly from rates at which they were consumed. In the fledging period, based on relative abundances, adult House Sparrows were taken less often than expected while juveniles were eaten more often than expected by Merlins. Twenty-seven Merlins were radio-tracked. Mean hunting range sizes of resident (hatched in the city) and immigrant (presumed to have hatched outside the city) males were 6.3 ± 1.3 (SE) km2 and 33.7 ± 12.1 km2, respectively. Mean hunting range sizes of resident and immigrant females were 6.6 ± 3.4 km2 and 8.6 ± 1.6 km2, respectively. Merlins that hunted exclusively in the city used all habitats in proportion to availability. Merlins that hunted both in and outside the city usually avoided hunting in agricultural areas, which were relatively low in prey abundance. During the incubation and nestling periods, males with more prey birds in their ranges had significantly smaller hunting ranges. Male Merlins with more prey birds in their ranges spent relatively less time hunting and males with larger broods spent more time hunting compared to those with smaller broods. For female Merlins, hunting range sizes were inversely correlated with both body mass and House Sparrow abundance.